BeeWS: honeybee-inspired, large-scale routing protocol for wireless sensor networks (WSNs). (2018) - Çelik, Fatih; Zengin, Ahmet
Recently, scalable routing protocols using swarm intelligence (SI), which are designed and evolved for wireless sensor networks (WSNs), have become a research trend in literature. This paper presents an optimal method based on SI inspired by honeybees. This method has minimum energy consumption, self-organisation, and support for a large-scale, autonomous individuals that detect the best route. In this paper, we propose a new energy-aware, scalable, and robust routing algorithm called Bee wireless sensor (BeeWS) inspired by honeybee foraging behaviour. This study consists of three parts: (1) honeybee behaviours are modelled and these behaviours are adapted to the structure of WSN; (2) routing protocol criteria are determined using this model and (3) the developed model is tested in a simulation environment based on discrete event system specification (DEVS) in order to simulate and model WSN behaviours and compare to other SI based on WSN routing protocols.